Efficacy of Balloon Guide Catheter-Assisted Thrombus Repair in Stroke Treatment: A Retrospective Survey in China. (28th September 2022) - Li, Qiang; Zhou, Tengfei; He, Yingkun; Guan, Min; Li, Zhaoshuo; Wu, Liheng; Wen, Changming; Wang, Haibo; Feng, Guang; Wang, Ziliang; Zhu, Liangfu; Li, Tianxiao
Abstract : Background . The first-pass (FP) effect, defined by successful cerebral reperfusion from a single pass of an endovascular stentriever, was associated with shorter procedural times and possible improved outcomes in patients with ischemic stroke secondary to large vessel occlusion. The adjunctive use of balloon guide catheter (BGC) may increase the rates of the first-pass effect. In this retrospective study we examined the impact of BGC on the first-pass effect in acute stroke patients. Methods . We included patients with acute ischemic stroke with large vessel occlusion treated by endovascular thrombectomy from 2018 to 2019. We categorized the cases into BGC and non-BGC groups. Differences in time metrics and outcomes were compared. Result . One hundred and thirty-two patients were included, and sixty-two were in BGC group (47.0%). The median procedural time was shorter (83.0 minutes vs 120.0 minutes, P = 0.000 ), and FP rate was higher in BGC group (58.1% vs 32.9%, P = 0.004 ) compared with non-BGC group. Proportion of modified Thrombolysis in Cerebral Infarction (mMTICI) 3 was higher (66.1% vs 37.1%, P = 0.001 ), and modified Rankin Scale (mRS) 0 to 2 was higher (59.7% vs 41.4%, P = 0.036 ) in BGC group compared with non-BGC group. In addition, BGC was associated with successful reperfusion odds ratio, 0.383; 95% confidence interval: 0.174-0.847; P = 0.018 ). The FP rate of BGC in the distal ICA was higher than that in the proximal ICA (87.5% vs 39.5%, P = 0.000 ), and the good clinical outcome rate at 90 days in the distal ICA was also higher than that in the proximal ICA (91.7% vs 39.5%, P = 0.000 ). Conclusion . We showed that BGC shortened the procedural time and increased the rate of the successful FP. We recommend that BGC could be considered the preferred technique for endovascular intervention in stroke.